2019
DOI: 10.1177/1087054719886359
|View full text |Cite
|
Sign up to set email alerts
|

High Yield of Screening for ADHD in the Epilepsy Monitoring Unit

Abstract: Objective: ADHD is common in patients with epilepsy, but adult patients with possible epilepsy are not routinely screened for ADHD. We aimed to characterize the results of two validated screening tools in the setting of an Epilepsy Monitoring Unit (EMU). Method: This study utilized the validated Adult ADHD Self-Report Scale version 1.1 (ASRS) and Conners Continuous Performance Test, third edition (CPT-III) to screen patients who were admitted to the EMU at a Level 4 epilepsy center. Patients with epileptic sei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 36 publications
0
17
0
Order By: Relevance
“…Recent literature has shown that ADHD is not only a common comorbidity with epileptic seizures but also with PNES (Say et al., 2015 ; Simani et al., 2020 ). Our prior study found that out of all patients diagnosed with PNES, 63.6% screened positive using the Adult ASRS, compared to 27.8% in patients with ES (Dunbar et al., 2019 ). Our current study is consistent with this previous work, where PNES patients were found to have an admission diagnosis of ADHD at a greater rate than PWE, although this difference was not statistically significant (Table 1 ).…”
Section: Discussion/conclusionmentioning
confidence: 97%
See 1 more Smart Citation
“…Recent literature has shown that ADHD is not only a common comorbidity with epileptic seizures but also with PNES (Say et al., 2015 ; Simani et al., 2020 ). Our prior study found that out of all patients diagnosed with PNES, 63.6% screened positive using the Adult ASRS, compared to 27.8% in patients with ES (Dunbar et al., 2019 ). Our current study is consistent with this previous work, where PNES patients were found to have an admission diagnosis of ADHD at a greater rate than PWE, although this difference was not statistically significant (Table 1 ).…”
Section: Discussion/conclusionmentioning
confidence: 97%
“…Future research can be aimed at providing a more streamlined ability to screen, diagnose, and treat patients with seizures and comorbid ADHD. The Adult ASRS is useful in screening for ADHD in this population (Dunbar et al., 2019 ). While the ASRS does not formally diagnose a patient with ADHD, it may be used as a tool along with other clinical factors to assess which patients require further formal evaluation for ADHD (Chamberlain et al., 2021 ).…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…One possibility is that focal seizures are more likely to be acquired later in life secondary to a focal injury, which may preclude the neurodevelopmental profile expected from patients with ADHD. In addition, patients with unknown etiologies due to negative MRI and EEG may be more likely to have psychogenic non-epileptic seizures, which we have previously found to have a higher likelihood of screening positive with the ASRS-v1.1 than patients with epilepsy in an Epilepsy Monitoring Unit (EMU) setting (Dunbar et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Patients who screened positive for ADHD using the ASRS criteria were also found to have an increased prevalence of comorbid psychogenic non-epileptic seizures (PNES) compared to epileptic seizures in the epilepsy monitoring unit (EMU) [21]. This provides further compounding evidence that ADHD is often comorbid with other psychiatric conditions.…”
Section: Screening For Adhdmentioning
confidence: 99%
“…These acute stressors commonly affecting children at this age include tense interpersonal relationships between siblings and marriage difficulties between parents. The diagnosis of ADHD in adolescents greater than the age of 12 is less common, therefore physicians should be vigilant when screening for these acute stressors including school bullying and depression[21]. First-line treatment for ADHD in preschool-aged children (4-5 years old) is behavioral therapy administered by parents or teachers.…”
mentioning
confidence: 99%